(untitled) (Journal of the Bangladesh Agricultural University, 2012)
We studied anatomy and histology of different segments of the digestive tract in postnatal growing broiler chickens with regard to their location, shape, size and weight. A group of four chickens, each at day 1 (D1), days 14 (D14) and days 28 (D28), total 12, were killed, their digestive tracts were dissected and described and shape, size and weight of different segments were recorded. Samples from different segments were prepared and stained with haematoxylin and eosin staining technique to study the histology under light microscope. The average lengths (cm) and weights (gm) of esophagus, proventriculus (glandular stomach), gizzard (muscular stomach), small intestine and large intestine were significantly higher (P<0.01) in chickens at D28 than that at D14 and at D1. The histological layers of digestive tract were lamina epithelia, lamina propria, lamina muscularis, submucosa, tunica muscularis and serosa with the exception in esophagus where outer adventitia was found. The esophageal glands were significantly more in numbers at D1 (in cross section, 12 in number per focus under 100x) than at D14 (6 in number per focus under 100x) and at D28 (2 in number per focus under 100x). The proventriculus consisted of macroscopic papillae with numerous microscopic folds with lamina propria comprised of simple glands, which converged into a common cavity near the surface. In gizzard, the cuticle, in the form of wavy lines ran parallel to the surface. The villi of small intestine and large intestine were lined by simple columnar epithelium. The apical parts of villi of the duodenum were slightly pointed and the basal parts of the villi were thicker than jejunum and ileum, whereas, the villi of the jejunum and ileum became shorter and broader than duodenum and most of the villi had blunt apical part and the basal parts were wider. The numbers of goblet cells were numerous in number in ileum than duodenum and jejunum. Plicae ran along the inner surface of the distal two thirds of the cacea. However, in the colorectum, the villi appeared as numerous long flat leaf-shaped structures which filled a large proportion of the lumen. The average lengths and widths of villi of small and large intestine were significantly higher (P<0.01) in chickens at D28 than that at D14 and at D1. The number of goblet cells in lamina epithelium and intestinal glands of the lamina propria were numerous in number at D28 than the chickens at D14 and at D1. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12096 J. Bangladesh Agril. Univ. 10(1): 6977, 2012